Pengembangan Aplikasi Audit Satuan Pengawasan Internal UIN Sunan Kalijaga Yogyakarta - Muhammad Galih Wonoseto (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
In carrying out internal supervision duties, SPI UIN Sunan Kalijaga Yogyakarta innovates by carrying out digital document-based supervision using the Google Drive service. SPI auditors often felt problems in using Google Drive, namely having to check the completeness of financial accountability documents manually one by one by opening a file on Google Drive. One of the goals of developing this application is to facilitate SPI auditors in checking the completeness of financial accountability report documents. The problems can be solved by creating an audit application. The audit application has been developed using the FAST method. Central admin, SPI admin, operator, superior operator, auditor, team leader, technical controller, and Head of SPI are user access rights in this application. The developed application has met the minimum requirements of SPI UIN Sunan Kalijaga Yogyakarta. Other universities can adopt this application.